Some Metrological Limitations to Rain Impact Computation in Storm Erosivity as Defined in the Revised Universal Soil Loss Equation, Version 2 (RUSLE2) - Casazza, Marco (Journal of Environmental Accounting and Management, 2026)
The theoretical and the instrumental metrological basis for computation of rainfall impact in storm erosivity as defined in the Revised Universal Soil Loss Equation, version 2 (RUSLE2) are considered. The present determination of rainfall erosivity is based on two factors: E, representing the rainfall kinetic energy, and I30, the maximum 30-minutes intensity for a given precipitation event. The present short review evidences some of the existing metrological limitations: (1) the non separation between the impact of falling rain and shallow flow of water; (2) the use of a non-universal semiempirical approach, (3) the absence of a clear model with respect to rain flow, runoff and soil wetting; (4) the use of a hybrid measure unit; (5) the intrinsic limitation of measuring technologies. The improvement of the existing parameter calculation techniques or a transition from a prevailing semi-empirical to a mainly physical-based approach would be desirable, even if this transformation shouldn’t affect the usability of the developed tools for practitioners.